Relationship between Trypanosoma brucei rhodesiense genetic diversity and clinical spectrum among sleeping sickness patients in Uganda - Kato, Charles D.; Mugasa, Claire M.; Nanteza, Ann; Matovu, Enock; Alibu, Vincent P. (BMC Research Notes, 2017)
Human African trypanosomiasis (HAT) due to Trypanosoma brucei rhodesiense in East and southern Africa is reported to be clinically diverse. We tested the hypothesis that this clinical diversity is associated with a variation in trypanosome genotypes. Trypanosome DNA isolated from HAT patients was genotyped using 7 microsatellite markers directly from blood spotted FTA cards following a whole genome amplification. All markers were polymorphic and identified 17 multi-locus genotypes with 56% of the isolates having replicate genotypes. We did not observe any significant clustering between isolates and bootstrap values across major tree nodes were insignificant. When genotypes were compared among patients with varying clinical presentation or outcome, replicate genotypes were observed at both extremes showing no significant association between genetic diversity and clinical outcome. Our study shows that T. b. rhodesiense isolates are homogeneous within a focus and that observed clinical diversity may not be associated with parasite genetic diversity. Other factors like host genetics and environmental factors might be involved in determining clinical diversity. Our study may be important in designing appropriate control measures that target the parasite.
Keywords: Trypanosoma brucei rhodesiense; Genetic diversity; Clinical spectrum; Sleeping sickness patients